Prevalence and characterisation of antibiotic resistance of Vibrio parahaemolyticus from seafood in Selangor, Malaysia / Vengadesh Letchumanan - Vengadesh, Letchumanan (2019)
Aquaculture industry has been professed as one of the fast-growing industries that serves a major source of seafood and revenue to many countries worldwide. Despite the nutritional benefits of seafood consumption, health risks linked to seafood consumption cannot be disregarded. Microbiological safety of seafood is of global concern recent years due to occurrence of seafood-borne cases and increase reports on antibiotic resistance among Vibrio parahaemolyticus isolated from seafood. The emergence of antimicrobial resistant V. parahaemolyticus poses treat to human health. In regard to increase reports on V. parahaemolyticus as a causative agent of seafood-borne illness, the study aimed to enumerate and characterise the antibiotic resistance profiles of V. parahaemolyticus isolated from seafood. A total of 770 seafood samples namely shrimp and shellfish were collected from both local wetmarket and supermarket in Selangor. The enumeration and identification using microbiological plating method on selective agar, thiosulphate citrate bile salt sucrose (TCBS) agar revealed that all seafood samples collected from wetmarket and supermarket sites were contaminated with Vibrio sp. The seafood samples analyzed had a microbial load of 2.29 log CFU/g to 6.63 log CFU/g. The toxR-PCR assay identified positive amplification of toxR gene in 50% (385/770) of the presumptive isolates. 32/385 (8.3%) isolates harboured the thermostable-related direct haemolysin (trh) gene and none with thermostable direct hemolysin (tdh) gene. The antibiotic susceptibility test revealed a total of 102 different types of antibiograms profiles among the V. parahaemolyticus isolates. The isolates were seen to be resistant to at least one type of antibiotic tested with MAR index ranged from 0 to 0.79. The chloramphenicol (catA2) gene was detected in 18/22 chloramphenicol-resistant isolates and 18/193 kanamycin-resistant isolate was positive for kanamycin aphA-3 gene. Further analysis on the plasmid profiles of V. parahaemolyticus isolates revealed 1-7 plasmids, with sizes ranging from 1.2kb to 10kb. There was no correlation seen between the plasmid profiles and antibiotic resistance patterns. Even within the isolates with same resistance profiles, the plasmid profiles were different and a few isolates even did not exhibit any plasmids. The isolates either demonstrated plasmidial or chromosomally mediated antibiotic resistance after plasmid curing assay. In conclusion, the results demonstrate that all the seafood samples collected are contaminated with V. parahaemolyticus regardless the sampling location and some of which carried the trh-gene which are potential to cause foodborne illness. The occurrence of multidrug resistance emphasizes the importance of study of antibiotic susceptibility of V. parahaemolyticus. Hence, constant monitoring of the prevalence and characterisation of resistance profiles of V. parahaemolyticus is needed to ensure food safety and human wellbeing.